2001
DOI: 10.1029/2000jc900008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of absorption by dissolved material at a continental shelf

Abstract: Abstract. Optical properties of dissolved (colored dissolved organic material (CDOM)) and particulate matter and hydrographic measurements were obtained at the Mid-Atlantic Bight during the fall of 1996 and the spring of 1997 as part of the Coastal Mixing and Optics experiment. To assess the temporal and spatial variability, time series were obtained at one location and cross-shelf transects were carried out. On short timescales, variability in the vertical distribution of the dissolved fraction was mostly due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 20 publications
3
64
0
7
Order By: Relevance
“…However, the qPCR data also indicated higher abundance of AAP bacteria in waters with higher light attenuation. Light attenuation is due to a combination of factors, including the presence of colored dissolved organic matter (9,11) and suspended particles (6,7). In the Baltic, bChl a and colored dissolved organic matter concentrations were positively correlated (26), suggesting an inverse relationship of AAP bacterial abundance with light.…”
Section: Discussionmentioning
confidence: 99%
“…However, the qPCR data also indicated higher abundance of AAP bacteria in waters with higher light attenuation. Light attenuation is due to a combination of factors, including the presence of colored dissolved organic matter (9,11) and suspended particles (6,7). In the Baltic, bChl a and colored dissolved organic matter concentrations were positively correlated (26), suggesting an inverse relationship of AAP bacterial abundance with light.…”
Section: Discussionmentioning
confidence: 99%
“…CDOM in the Ems (at 440 nm) was found to absorb over 2 m ¡1 , while the median absorption over the Wadden Sea area in spring, summer and autumn was 0.64 m ¡1 (Table 1) (Hommersom et al 2009). In the shallow Wadden Sea, pore water adds to the CDOM concentration Boss et al 2001;Laane and Kramer 1990), while sand beds were found to work as a sink for organic matter that can Wlter the entire water body of the Wadden Sea within 3-10 days (De Beer et al 2005). Still, maps of CDOM concentrations over the entire Wadden Sea area as in Hommersom et al (2009) are sparse.…”
Section: ¡1mentioning
confidence: 99%
“…On local scales, in situ production from phytoplankton decomposition and extraction from bottom sediments may be an important source of CDOM (Twardowski and Donaghay, 2001;Boss et al, 2001). However, in their studies, Rochelle-Newall and Fisher (2002 a) showed that CDOM absorption doesn't correlate with chlorophyll_a content.…”
Section: Post-monsoonmentioning
confidence: 99%